Hemolytic activity of alternative complement pathway as an indicator of innate immunity in pacu (Piaractus mesopotamicus) - Biller-Takahashi, Jaqueline Dalbello [UNESP]; Takahashi, Leonardo Susumu [UNESP]; Marzocchi-Machado, Cleni Mara; Zanuzzo, Fabio Sabbadin [UNESP]; Sabioni, Rafael Estevan [UNESP]; Urbinati, Elisabeth Criscuolo [UNESP] (Sociedade Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the methodology to establish the hemolytic activity of alternative complement pathway as an indicator of the innate immunity in Brazilian fish pacu (Piaractus mesopotamicus), in addition to verifying the influence of β-glucan as an immunostimulant. Fish were fed with diets containing 0, 0.1 and 1% β-glucan, during seven days, and then inoculated with Aeromonas hydrophila. Seven days after the challenge, they were bled for serum extraction. The methodology consisted of a kinetic assay that allows calculating the required time for serum proteins of the complement to promote 50% lysis of a rabbit red blood cell suspension. The method developed in mammals was successfully applied for pacu and determined that the hemolytic activity of the proteins of the complement system (alternative pathway) increased after the pathogen challenge, but was not influenced by the β-glucan treatment.
Keywords: A. hydrophila; β-glucan; immune response; pacu